Graphene-Enhanced Surface Plasmon Resonance Liquid Refractive Index Sensor Based on Photonic Crystal Fiber - Li, Bin (Sensors (Basel), 2019)
A surface plasmon resonance (SPR) liquid refractive index sensor based on photonic crystal fiber (PCF) is proposed. The PCF is made of the exposed core structure, and the gold film is formed by electron beam evaporation within its defects. The sensitivity of the sensor is improved by coating graphene on the surface of the gold film. The experimental results show that the sensitivity of the sensor is increased by 390 nm/RIU after the introduction of graphene, and finally to 2290 nm/RIU. The experiment and simulation have a good consistency. Significantly, the sensor can be reused, and the measurement accuracy can be maintained.